SINTESIS DAN OPTIMALISASI GEL KITOSAN-ALGINAT - Sugita, Purwantiningsih; Sjachriza, Achmad; wahyono, dwi (Badan Pengkajian dan Penerapan Teknologi, 2007)
Shrimp shell can be used to make chitosan. The objective of this work is to sythesis and optimize chitosan-alginate gel by comparing its rheological properties. Rheological properties of chitosan were improved by gelation using glutaraldehyde as cross linker and natural hydrocolloids such as alginate. Rheological properties measured were strength, break point, rigidity, swelling and shrinking gel. The gel was made by mixing chitosan solution 2.5% (w/v), glutaraldehyde 4%, 5%, and 6% (v/v), and alginate 0%, 0.75%, and 1.0%. According Modde 5, the optimum gel happened at glutaraldehyde and alginateconcentration are 4.0% and 0.82%, respectively. This optimalization to adsorp metal ions gave gel strength, break point, pembengkakan, rigidity and shrinking properties are 881,4385 g cm-2, 1,0267 cm, 4,5313 g, 8,5179 g cm-1 and 1,6280 g, respectively.